PERENCANAAN STRATEGIK PENDIDIKAN KARAKTER DALAM MEMBANGUN 7 KEBIASAAN ANAK INDONESIA HEBAT DI SMAN 1 JATILUHUR KECAMATAN JATILUHUR KABUPATEN PURWAKARTA - Jahroni Hartanto, Bobby; Syahputra, Darto; Nurdin , Ali; Yuniar , Isny; Handayani, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe and analyze the implementation of strategic planning in strengthening character education through the development of the 7 Habits of Great Indonesian Students at SMAN 1 Jatiluhur, Purwakarta. Using a qualitative descriptive approach and a case study method, data were collected through interviews, observations, and document analysis. The results indicate that the school has initiated strategic character education planning by integrating values such as discipline, independence, responsibility, and social care through daily habits. The strategic planning has been outlined in the school's vision, mission, and operational curriculum. However, the implementation still faces challenges, particularly in organizing, monitoring, and evaluating the program. There is no formal character education team, and assessments are not yet based on measurable indicators. The findings suggest that effective strategic character education requires strong institutional support, structured planning, and ongoing evaluation to build a sustainable culture of character in schools. Keywords: Strategic Planning, Character Education, 7 Habits, School Culture, Educational Management